2016
DOI: 10.1099/jmm.0.000219
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbapenem-resistant Acinetobacter calcoaceticus–baumannii complex isolates from nosocomial bloodstream infections in southern Iran

Abstract: Acinetobacter baumannii is an important opportunistic bacterial pathogen responsible for serious infections in hospitalized patients. From a total of 78 consecutive non-repetitive Acinetobacter spp. isolates from patients with blood infections, 61 were carbapenem resistant, which were positive for bla OXA-51-like (96.7 %), bla OXA-23-like (77 %), bla OXA-58-like (8.1 %) and bla OXA-40-like genes (32.8 %) by multiplex PCR. The isolates were identified as A. baumannii (n559) and Acinetobacter nosocomialis (n52).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…(100%), VRE (85.7%), and Enterobacteriaceae (74.2%). These numbers are in agreement with those in other studies investigating the etiology of nosocomial infections in Iran 3,36,37 . Infections caused by MDR bacteria are progressively growing in the care of solid organ transplant recipients worldwide and indeed, the emergence of various MDR pathogens all over the world represents a global threat 38 .…”
Section: Discussionsupporting
confidence: 90%
“…(100%), VRE (85.7%), and Enterobacteriaceae (74.2%). These numbers are in agreement with those in other studies investigating the etiology of nosocomial infections in Iran 3,36,37 . Infections caused by MDR bacteria are progressively growing in the care of solid organ transplant recipients worldwide and indeed, the emergence of various MDR pathogens all over the world represents a global threat 38 .…”
Section: Discussionsupporting
confidence: 90%
“…could be attributed to its genome plasticity that allows the acquisition and loss of mobile genetic elements (plasmids, transposons) that modifies the organism’s genomic structure (Savari et al, 2017). As for non baumannii species, only one study reported the detection of OXA-23 and SPM producing Acinetobacter nosocomialis in patients with blood infections (Pourabbas et al, 2016). In P. aeruginosa , MBLs were the most common carbapenemases including: IMP (IMP-1 and IMP-55) and VIM variants (VIM-1, VIM-2) (Abiri et al, 2015; Lari et al, 2015; Mirbagheri et al, 2015; Moosavian and Rahimzadeh, 2015; Azizi et al, 2016; Saffari et al, 2016; Kazeminezhad et al, 2017; Dogonchi et al, 2018; Pournajaf et al, 2018; Rostami et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…The first three are implicated in infections, while the latter is rarely considered pathogenic. 8 It appears as Gram-negative coccobacillus in pairs ranging from 1 to 1.5 µm when observed under the microscope after gram staining. It often resists complete decolorization and can deceive as Gram-positive cocci.…”
Section: Introductionmentioning
confidence: 99%